The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1248/bpb.20.338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mitragynine on cAMP Formation Mediated by .DELTA.-Opiate Receptors in NG108-15 Cells.

Abstract: Mitragynine, a major constituent of the young leaves of Mitragyna speciosa KORTH., has been reported to exert antinociceptive activity in mice. To determine the mechanism the influence of mitragynine on cAMP content was measured in NG108-15 cells which possess delta opioid receptors and alpha 2B-adrenoceptors. Mitragynine inhibited the forskolin-stimulated cAMP content in a concentration dependent manner as well as morphine and noradrenaline. Mitragynine- and morphine-induced inhibition of cAMP content were bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Corynantheidine also binds at μ-receptors but acts as a functional antagonist since it does not activate this receptor [8]. In addition to the opioid receptor-mediated effects, there are conflicting data on the effect of mitragynine on α 2 and HT 2A receptors [12][13][14]. Kratom is often said to have coca-like effects (first described in 1932 [15]), but except the increased ability to work, there is little evidence for amphetamine-like effects and the possible pharmacological mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Corynantheidine also binds at μ-receptors but acts as a functional antagonist since it does not activate this receptor [8]. In addition to the opioid receptor-mediated effects, there are conflicting data on the effect of mitragynine on α 2 and HT 2A receptors [12][13][14]. Kratom is often said to have coca-like effects (first described in 1932 [15]), but except the increased ability to work, there is little evidence for amphetamine-like effects and the possible pharmacological mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study of the effect of mitragynine (1) on cAMP formation in NG108-15 cells possessing d-opioid receptors and a2B-adrenoceptors has suggested that mitragynine (1) acts directly on opioid receptors but not on a2-adrenoceptors, to show antinociceptive activity. 32) An investigation of the effects of mitragynine (1) on the head-twitch response induced by 5-methoxy-N,N-dimethyltryptamine in mice indicated that the stimulation of postsynaptic a2-adrenoceptor, the blockade of 5-HT 2A receptors, or both, are involved in the suppression of 5-HT 2A receptor mediated head-twitch response by mitragynine. 33) In addition, it was suggested that antinociception caused by i.c.v.…”
Section: )mentioning
confidence: 99%
“…The 1 H-and 13 C-NMR spectra of 4 clearly showed the presence of two sets of the fundamental structural units in the mother compound, mitragynine (1), i.e., two b-methoxyacrylic acid methyl ester residues, two ethyl groups and two 9-methoxy groups on the aromatic ring. Further, the presence of one acetoxy group was shown by the 1 H-NMR (d 2.09, 3H, s) and 13 C-NMR (d 168.3, 20.8) spectra. In the 13 C-NMR spectrum, two characteristic signals due to indolenine carbons at C-2 or C-2Ј (d 187.1, 181.1) as well as two newly formed quaternary carbons at C-7 or C-7Ј (d 61.7, 84.5) were observed.…”
Section: Resultsmentioning
confidence: 94%
“…
In the recent chemical [1][2][3][4][5][6][7][8][9] and pharmacological [10][11][12][13][14][15] studies on the Rubiaceous plant, Mitragyna speciosa, [16][17][18][19][20] which has been traditionally used in tropical areas as a substitute for opium, 21) we have found that mitragynine (1), a major Corynanthe-type indole alkaloid of this plant, exhibited potent analgesic activity mediated by m-and d-opioid receptors.
22)Further, 7-hydroxymitragynine (3), 23) an oxidative derivative of 1, was found as a novel opioid agonist with higher potency than that of morphine.24) This remarkable opioid ligand was prepared from mitragynine (1) by conventional procedure, i.e., oxidation of 1 with lead tetraacetae [Pb(OAc) 4 ] followed by alkaline hydrolysis of the resultant 7-acetoxyindolenine (2). In investigating the first oxidation step in detail, we found a structurally and mechanistically novel dimerization product, as described in this publication.
Results and Discussion

In general, 7-acetoxyindolenine derivatives are prepared from the corresponding indoles by oxidation with Pb(OAc) 4 .

…”
mentioning
confidence: 99%
See 1 more Smart Citation